2021
DOI: 10.1136/bjophthalmol-2021-319618
|View full text |Cite
|
Sign up to set email alerts
|

Big-data and artificial-intelligence-assisted vault prediction and EVO-ICL size selection for myopia correction

Abstract: AimsTo predict the vault and the EVO-implantable collamer lens (ICL) size by artificial intelligence (AI) and big data analytics.MethodsSix thousand two hundred and ninety-seven eyes implanted with an ICL from 3536 patients were included. The vault values were measured by the anterior segment analyzer (Pentacam HR). Permutation importance and Impurity-based feature importance are used to investigate the importance between the vault and input parameters. Regression models and classification models are applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 29 publications
5
56
0
Order By: Relevance
“…In addition, artificial intelligence has been used to try to perform ICL size selection in recent years. Shen et al [ 27 ] trained and validated several machine learning models by a 3536-patient database and found that the random forest model had the highest fitting degree ( R 2 = 0.315) and the best prediction accuracy (82.8%); obviously, this result was not entirely satisfactory. A similar situation also appeared in the research by Kamiya et al [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, artificial intelligence has been used to try to perform ICL size selection in recent years. Shen et al [ 27 ] trained and validated several machine learning models by a 3536-patient database and found that the random forest model had the highest fitting degree ( R 2 = 0.315) and the best prediction accuracy (82.8%); obviously, this result was not entirely satisfactory. A similar situation also appeared in the research by Kamiya et al [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…AI technology also have applications in refractive surgery. Methods like random forest, gradient boosting, XGBoost, and SVM regression (SVR) can assist in implant size selection and arch height prediction in ICL surgery ( Kamiya et al, 2021 ; Kang et al, 2021 ; Shen et al, 2021 ). Proper sizing ensures a safe postoperative ICL dome and reduces complications such as angle-closure glaucoma and anterior subcapsular cataract.…”
Section: Ai Technology In Myopia Treatmentmentioning
confidence: 99%
“…Visian ICL comes in spherical powers from −18.0 to +10.0 diopters, and there is a toric variant from +0.5 to +6.0 diopters of the cylinder. The ICL is produced in four sizes, 12.1 mm, 12.6 mm, 13.2 mm, and 13.7 mm to fit the size of the sulcus of the patient as best as possible [92,97]. STAAR Surgical Visian ICL is a great option for patients that are not suitable candidates for corneal refractive surgery and are not ready for refractive lens exchange due to their age.…”
Section: Posterior Chamber Piolsmentioning
confidence: 99%